2003
DOI: 10.21273/hortsci.38.6.1227
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and Topdressing Requirements for Thatch Management in A and G Bentgrasses and Creeping Bluegrass

Abstract: Empirical observations suggest certain new cultivars of creeping bentgrass (Agrostis stolonifera L.) with high shoot density require more intensive topdressing and core aeration to control thatch compared to less dense cultivars such as `Penncross. In addition, a variety of Poa annua var. reptans Hausskn., `DW-184, has recently been released for putting green use but management requirements are undocumented. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 4 publications
(4 reference statements)
7
28
0
Order By: Relevance
“…Previous research found similar amounts of sand topdressing incorporation into Penn A and G series creeping bentgrass using brushing alone as this study found on ultradwarf bermudagrass when topdressing using brushing + vibratory rolling (25). Stier and Hollman (25) found that 1 to 3% of topdressing applied to Penn A and G series bentgrass was removed by mowing after being incorporated by brushing alone, which was similar to the amounts of topdressing sand removed after brushing + vibratory rolling on ultradwarf bermudagrass. This amount was hypothesized to have little effect on practitioners (25).…”
Section: Incorporation Methods Effects On Putting Green Characteristicssupporting
confidence: 74%
See 4 more Smart Citations
“…Previous research found similar amounts of sand topdressing incorporation into Penn A and G series creeping bentgrass using brushing alone as this study found on ultradwarf bermudagrass when topdressing using brushing + vibratory rolling (25). Stier and Hollman (25) found that 1 to 3% of topdressing applied to Penn A and G series bentgrass was removed by mowing after being incorporated by brushing alone, which was similar to the amounts of topdressing sand removed after brushing + vibratory rolling on ultradwarf bermudagrass. This amount was hypothesized to have little effect on practitioners (25).…”
Section: Incorporation Methods Effects On Putting Green Characteristicssupporting
confidence: 74%
“…Stier and Hollman (25) found that 1 to 3% of topdressing applied to Penn A and G series bentgrass was removed by mowing after being incorporated by brushing alone, which was similar to the amounts of topdressing sand removed after brushing + vibratory rolling on ultradwarf bermudagrass. This amount was hypothesized to have little effect on practitioners (25). However, the amounts of topdressing sand removed by brushing alone or vibratory rolling in this study were larger than those found in the previous study (25) and could lead to mowing equipment damage and poor playing conditions.…”
Section: Incorporation Methods Effects On Putting Green Characteristicsmentioning
confidence: 72%
See 3 more Smart Citations